Application of Preference Selection Index Method in DSS for Determining Recipients of BLT-DD - Khasanah, Lutfa Nur; Winiarti, Sri (International Journal of Informatics and Computation, 2026)
The determination of Village Fund Direct Cash Assistance (BLT-DD) recipients at the village level often relies on manual procedures and subjective judgment, which can lead to inaccurate beneficiary selection and unequal aid distribution. This study implements the Preference Selection Index (PSI) method in a web-based Decision Support System (DSS) to support a more objective, transparent, and accountable BLT-DD recipient selection process in Lemahireng Village. We evaluate it using data from 40 prospective beneficiaries based on eight criteria: monthly income, number of dependents, age, housing status, vehicle ownership, occupation, history of chronic illness, and electricity capacity. This experiment selects the PSI method because it automatically determines criterion weights from data variation, eliminating the need for subjective weighting by decision-makers. We evaluate the proposed system through black-box testing, expert judgment, usability testing using the System Usability Scale (SUS), and a comparison with the Simple Additive Weighting (SAW) method. The black-box testing results show that all system functions operate according to the specified requirements. The expert judgment evaluation achieves a conformity rate of 75% between the system recommendations and the assessments of village officials. In addition, the usability evaluation produces a SUS score of 85.71, which falls into the Excellent category. The comparison between PSI and SAW generates identical ranking positions, confirming the consistency of the proposed approach while preserving the advantage of objective weight determination.